2021
DOI: 10.1111/os.12915
|View full text |Cite
|
Sign up to set email alerts
|

TiRobot‐Assisted Percutaneous Cannulated Screw Fixation in the Treatment of Femoral Neck Fractures: A Minimum 2‐Year Follow‐up of 50 Patients

Abstract: Objective To assess the long‐term clinical efficacy of TiRobot‐assisted percutaneous cannulated screw fixation in the treatment of femoral neck fractures. Methods This retrospective study included 50 patients with unilateral femoral neck fractures who were treated with TiRobot‐assisted percutaneous cannulated screw fixation from September 2017 to May 2018. After at least 2 years of follow‐up, the results of treatment, including operation duration, frequency of fluoroscopy use, intraoperative bleeding, hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Duan et al [ 13 ] was a prospective cohort study, while He et al [ 14 ] and Wan et al [ 15 ] were the only randomized control trials. Wang et al (2019) [ 16 ] and Zhu et al (2021) [ 17 ] were the largest studies with 128 and 133 patients each compared to the other studies that had a number of included patients in the range of 3-60. The studies aimed to assess the efficacy and safety of the included studies looking mainly at intraoperative outcomes.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Duan et al [ 13 ] was a prospective cohort study, while He et al [ 14 ] and Wan et al [ 15 ] were the only randomized control trials. Wang et al (2019) [ 16 ] and Zhu et al (2021) [ 17 ] were the largest studies with 128 and 133 patients each compared to the other studies that had a number of included patients in the range of 3-60. The studies aimed to assess the efficacy and safety of the included studies looking mainly at intraoperative outcomes.…”
Section: Reviewmentioning
confidence: 99%
“…Overall, robot-assisted fixation is associated with fewer complications. The incidence of avascular necrosis is significantly greater in the conventional group compared to the robot-assisted group in Wang et al [ 16 ], He et al [ 14 ], and Zhu et al [ 17 ]. No significant differences were seen between the groups in other studies.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, robotic arms have been increasingly used in orthopaedic surgery to improve surgical accuracy, and reduce complications and radiation exposure to doctors 12 . Many studies have reported that TiRobot (TINAVI Medical Technologies Co., Ltd.), which is an orthopaedic surgical robotic system, has shown greater accuracy than conventional procedures in spinal surgery, helping to achieve good long‐term clinical efficacy in the treatment of femoral neck fractures 13,14 . The TiRobot orthopaedic surgical robot system uses intraoperative three‐dimensional CT reconstruction to display bony markers in the target area, using infrared tracking reference markers attached to the patient to carry out real‐time positioning of the surgical area, and the robotic arm to guide the operation path 15 .…”
Section: Introductionmentioning
confidence: 99%